Tama-ki-Hikurangi: A whare built for Te Kooti - Rangiwai, Byron (Te Kaharoa, 2021)
For the followers of the famous nineteenth-century prophet Te Kooti in Waiōhau, Tama-ki-Hikurangi is an integral part of their whakapapa, history, and theology. Patuheuheu are followers of Te Kooti and as such, the Ringatū faith—the religion that he created—is part of what it means to be Patuheuheu. While adherence to the faith has waxed and waned, the whare, Tama-ki-Hikurangi remains as a focal point of Patuheuheu’s historical connection to Te Kooti and the Ringatū faith. Indeed, the faithful still gathers in the whare most Saturdays to hold hāpati—sabbath-day prayers. Tama-ki-Hikurangi was built for Te Kooti, and its size and design is a direct result of Te Kooti’s syncretistic theology. This paper is an exploration of what is known about the whare from a Patuheuheu perspective.